Republicanismo histórico. Regeneracionismo y educación (1898-1903) - Capitán Díaz, Alfonso (Revista Española de Pedagogía, 2018)
The republicans at the end of the 19th century, with their «critical consciousness» and «institutionist» way of life (related to the Free Institution of Teaching), in some cases verge on scientific positivism, maintained, after the national disaster of 1898, that one of the main ways of regeneration for Spanish people, was educational reform. The Europeanization of the school, social equality by means of an adequate national education, autonomy of the universities, the whole training of students, «popular» education¿ were common places in the speeches and debates in Parliament, in scientific and literary atheneums, and in other academic and public opinion circles.
HJSTORICAL REPUBLICANISM, REGENERATION, ANO EDUCATION (1898-1903)
Keywords: republicanism; free institution of teaching; education and the national disaster of 1898; education and cultural diffussion; autonomy of the universities; Revista Española de Pedagogía